Irrationality or efficiency of macroeconomic survey forecasts? Implications from the anchoring bias test - Dieter Hess; Sebastian Orbe (University of Cologne, Centre for Financial Research (CFR), 2011)
We analyze the quality of macroeconomic survey forecasts. Recent findings indicate that they are anchoring biased. This irrationality would challenge the results of a wide range of empirical studies, e.g., in asset pricing, volatility clustering or market liquidity, which rely on survey data to capture market participants' expectations. We contribute to the existing literature in two ways. First, we show that the cognitive bias is a statistical artifact. Despite highly significant anchoring coefficients a bias adjustment does not improve forecasts' quality. To explain this counterintuitive result we take a closer look at macroeconomic analysts' information processing abilities. We find that analysts benefit from the use of an extensive information set, neglected in the anchoring bias test. Exactly this information advantage drives the misleading anchoring bias test results. Second, we find that the superior information aggregation capabilities enable analysts to easily outperform sophisticated timeseries forecasts and therefore survey forecasts should clearly be favored.
Keywords: G12; G14; G17; E17; E37; 330; macroeconomic announcements; efficiency of forecasts; anchoring bias; rationality of analysts